2011
DOI: 10.1111/j.1365-3040.2010.02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐related trends in sapwood biophysical properties in two conifers: avoidance of hydraulic dysfunction through coordinated adjustments in xylem efficiency, safety and capacitance

Abstract: In the Pacific north-west, the Cascade Mountain Range blocks much of the precipitation and maritime influence of the Pacific Ocean, resulting in distinct climates east and west of the mountains. The current study aimed to investigate relationships between water storage and transport properties in populations of Douglas-fir (Pseudotsuga menziesii) and ponderosa pine (Pinus ponderosa) adapted to both climates. Sapwood thickness, capacitance, vulnerability to embolism, and axial and radial conductivity were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 58 publications
3
69
2
1
Order By: Relevance
“…Consequently, greater sensitivity to water availability of Douglas-fir, but not ponderosa pine, in xeric sites most likely reflects known differences in hydraulic architecture and life history strategies of these two species and is consistent with the idea of an adaptive tradeoff between xylem efficiency and hydraulic safety (e.g. Pinol and Sala, 2000;Barnard et al, 2011).…”
Section: Species-specific Effects Of Habitat Type On Sensitivity To Cmentioning
confidence: 54%
See 1 more Smart Citation
“…Consequently, greater sensitivity to water availability of Douglas-fir, but not ponderosa pine, in xeric sites most likely reflects known differences in hydraulic architecture and life history strategies of these two species and is consistent with the idea of an adaptive tradeoff between xylem efficiency and hydraulic safety (e.g. Pinol and Sala, 2000;Barnard et al, 2011).…”
Section: Species-specific Effects Of Habitat Type On Sensitivity To Cmentioning
confidence: 54%
“…Ponderosa pine, on the other hand, has developed structural adaptations that allow it to avoid dangerously low water potentials. For example, Barnard et al (2011) found that ponderosa pine had almost twice the sapwood area supplying water to a given leaf area as Douglas-fir, leading to a 50% decrease in the pressure gradient required to conduct a given amount of water. Moreover, ponderosa pine, but not Douglas-fir, is able to significantly modify the ratio of biomass in leaf area relative to sapwood area (A L :A S ) across environmental gradients in response to increasing aridity (Delucia et al, 2000).…”
Section: Species-specific Effects Of Habitat Type On Sensitivity To Cmentioning
confidence: 98%
“…A recent study on Douglas-fir (Pseudotsuga menziesii) and ponderosa pine (Pinus ponderosa) showed that the vulnerability of sapwood to embolism is greater in populations of both species adapted to more arid environments (Barnard et al 2011). However, capacitance was also greater in these populations, suggesting that under conditions of high transpiration, xylem capacitance can play an important role in avoiding levels of tension that would cause excessive embolism.…”
Section: Discussionmentioning
confidence: 98%
“…1e-h). Similarly, Barnard et al (2011) found plasticity in C among conifers in forests that varied in rainfall, yet both species they studied had higher C at lowrainfall sites. Our result that C shifted to be higher or lower in the dry forest is consistent with either greater desiccation avoidance (higher C) or greater desiccation tolerance (lower C) in drier environments (discussed below).…”
Section: Variation In C Within and Among Species And Ontogenetic Stagesmentioning
confidence: 89%